Fenomena Gentrifikasi Digital dan Implikasinya terhadap Kesenjangan Ekonomi di Indonesia: Kajian Yuridis dan Perspektif Hukum Islam - Agus Rojak Samsudin; Ali Aminulloh (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
The rapid growth of Indonesia's digital economy has introduced opportunities and challenges, particularly for MSMEs (Micro, Small, and Medium Enterprises). This study investigates the phenomenon of digital gentrification and its role in exacerbating economic inequality. Using a multidisciplinary approach combining legal and Islamic perspectives, the study draws on secondary data from official reports and scholarly analyses. Findings reveal that while large enterprises dominate digital ecosystems with 70% of e-commerce transactions, MSMEs contribute only 12%, hindered by limited infrastructure and low digital literacy. Islamic principles of distributive justice and maqashid syariah offer a moral framework for addressing these disparities. Policy implications include enhanced infrastructure development, digital literacy programs, and leveraging Islamic finance mechanisms like zakat to promote inclusivity. This study enriches the discourse on digital inclusion and its role in fostering equitable economic growth, proposing actionable strategies to bridge digital divides and reduce systemic inequalitie.